Rho GTPases: Promising candidates for overcoming chemotherapeutic resistance. (10th April 2020) - Zheng, Chun-Wen; Zeng, Rui-Jie; Xu, Li-Yan; Li, En-Min
Abstract: Despite therapeutic advances, resistance to chemotherapy remains a major challenge to patients with malignancies. Rho GTPases are essential for the development and progression of various diseases including cancer, and a vast number of studies have linked Rho GTPases to chemoresistance. Therefore, understanding the underlying mechanisms can expound the effects of Rho GTPases towards chemotherapeutic agents, and targeting Rho GTPases is a promising strategy to downregulate the chemo-protective pathways and overcome chemoresistance. Importantly, exceptions in certain biological conditions and interactions among the members of Rho GTPases should be noted. In this review, we focus on the role of Rho GTPases, particularly Rac1, in regulating chemoresistance and provide an overview of their related mechanisms and available inhibitors, which may offer novel options for future targeted cancer therapy. Highlights: Rho GTPases are essential in tumorigenesis and chemoresistance by regulating apoptosis, DNA repairand drug uptake. Inhibiting Rho GTPases is promising in overcoming chemoresistance. Exceptions that Rho GTPases promote chemosensitivity exist in certain conditions. Inhibitors with higher efficacy and less toxicity are needed for clinical use.